America's human capital paradox - Thomas A. Kochan (W.E. Upjohn Institute for Employment Research, 2012)
It is widely recognized that human capital is essential to sustaining a competitive economy at high and rising living standards. Yet acceptance of persistent high unemployment, stagnant wages, and other indicators of declining job quality suggests that policymakers and employers undervalue human capital. This paper traces the root cause of this apparent paradox to the primacy afforded shareholder value over human resource considerations in American firms and the longstanding gridlock over employment policy. I suggest that a new jobs compact will be needed to close the deficit in jobs lost in the recent recession and to achieve sustained real wage growth.
Keywords: J01; J08; J53; 330; social contract; jobs compact; job growth; wages